Valor diagnóstico de biomarcadores hematológicos para predizer a síndrome respiratória aguda grave entre gestantes/puérperas hospitalizadas por covid-19 - Araújo, Renata Ito de (2023)
Coronavirus disease 2019 (COVID-19) is caused by the SARS-CoV-2 virus, which can lead to severe acute respiratory syndrome (SARS), with clinical manifestations ranging from mild to severe. Pregnant women may experience a more severe progression of COVID-19, including a higher frequency of fetal and neonatal complications, compared to non-pregnant women. Early identification of risk factors associated with severe outcomes is important to indicate preventive interventions for these complications. Objective: The present study aims to analyze the diagnostic value of hematological biomarkers measured at admission for predicting SARS in pregnant or postpartum patients hospitalized for COVID-19. Methods: Retrospective cohort study of pregnant/postpartum women who were hospitalized for COVID-19 at a university hospital in the Central Region of Brazil from March 2020 to October 2021. Medical records was analysed to obtain demographic, clinical, and laboratory information for all pregnant/postpartum women hospitalized during the study period. Leukocyte, neutrophil, lymphocyte, and monocyte counts, as well as the determination of neutrophil-lymphocyte ratio (NLR) and monocyte-lymphocyte ratio (MLR), were used to assess their potential diagnostic value for SARS among study participants. Results: A total of 126 patients were included, of whom 113 (89.7%) self-identified as mixed race, 41.3% were married, and the majority (75.4%) were aged 26 to 40 years. Among the comorbidities, diabetes mellitus (19%) and systemic arterial hypertension (17.5%) were the most prevalent. Invasive ventilatory support was required in 86 (68.3%) of pregnant/postpartum women, and 55 (43.6%) of them were diagnosed with SARS. Mean leukocyte and neutrophil counts were higher in patients with SARS (p<0.001) compared to those without this complication. On the other hand, the mean lymphocyte count was lower (p<0.001) in patients with SARS. NLR (p<0.001) and MLR (p<0.001) were also statistically associated with the incidence of SARS among study patients. Receiver operating characteristic (ROC) curves constructed from the hematological parameters assessed at hospital admission demonstrated high accuracies for diagnosing progression to SARS, with values of 74.5% for leukocyte count, 78.0% for neutrophil count, 70.1% for lymphocyte count, 86.1% for NLR, and 73.2% for MLR. At defined cutoff points, their sensitivities for predicting SARS were also satisfactory, at 67% for neutrophil count, 65% for MLR, and 81% for NLR. Conclusion: White blood cell, neutrophil, and lymphocyte counts, as well as NLR and MLR measured at hospital admission, showed satisfactory accuracy and sensitivity parameters for predicting pregnant/postpartum women at higher risk of developing SARS due to COVID-19. Due to their rapid and low-cost obtainment, they can be useful in clinical practice for prognostic evaluation of pregnant/postpartum women hospitalized for COVID-19.